Hepatitis C, A Global Issue: Access to Care and New Therapeutic and Preventive Approaches in Resource-Constrained Areas - Lemoine, Maud; Thursz, Mark (Seminars in Liver Disease, 2014)
With the advent of all oral direct-acting antiviral drugs with a broad range of genotypic activity and a low incidence of side effects, we are entering an exciting new era in the therapeutics of hepatitis C virus (HCV). However, it is not yet clear who will benefit from these innovations: Will the advantages be limited to HCV patients in industrialized nations or could the whole community of HCV-infected individuals be given access to treatment? As the majority of people infected with HCV live in resource-limited settings it is important to overcome the barriers that restrict access to treatment in these areas. Drug costs, public and professional education, simplified diagnostics, and political imperative all need to be addressed before the majority of HCV-infected individuals can benefit from the new generation of HCV antivirals.
Keywords: hepatitis C virus; chronic hepatitis C; prevalence; access to treatment; resource-limited countries; direct-acting antivirals